Factors influencing the participation of groups identified as underserved in cervical cancer screening in Europe: a scoping review of the literature - Rachel Greenley; Sadie Bell; Samuel Rigby; Rosa Legood; Victoria Kirkby; Martin McKee; the CBIG-SCREEN Consortium (Frontiers Media S.A., 2023)
BackgroundCervical cancer is a preventable and inequitably distributed disease. Screening plays a vital role in prevention, but many women face barriers to participation. The aims of this scoping review, undertaken to inform the co-design of interventions to equitably increase screening uptake, were to: (1) identify barriers and facilitators to cervical cancer screening for underserved populations, and (2) identify and describe the effectiveness of interventions aimed at improving participation in cervical cancer screening among underserved groups in Europe.MethodsQualitative, quantitative, and mixed methods studies focusing on barriers and facilitators to cervical screening participation and interventions to improve uptake undertaken in Europe and published after 2000 were included. Four electronic databases were searched to identify relevant papers. Titles and abstracts were screened, full text reviewed, and key findings extracted. Data were extracted and analyzed according to different health system strata: system-wide (macro), service specific (meso) and individual/community specific (micro). Within these categories, themes were identified, and the population groups impacted were recorded. All findings are presented in accordance with (PRISMA) guidelines.Results33 studies on barriers and facilitators and eight intervention studies met the inclusion criteria. Collectively, the findings of these studies presented a wide array of screening uptake barriers, facilitators, and interventions, predominantly related to screening service and individual/community factors. However, although diverse, certain core themes around information provision, prompts for participation and the need for inclusive spaces were apparent. Implementation of screening programs should focus on: (1) reducing identifiable barriers, (2) increasing public awareness, and (3) providing patient reminders and measures to promote engagement by healthcare providers.ConclusionThere are many barriers to uptake of cervical cancer screening and this review, nested within a larger study, will inform work to devise a solution alongside groups identified in three European countries.